Isolation of Saprolegnia aenigmatica oomycetes and protocol for experimental infection of pacu (Piaractus mesopotamicus) - Silvia Patrícia Carraschi (Acta Scientiarum. Biological Sciences, 2018)
Successful disease treatment depends on molecular studies under indoor conditions with experimental infection protocols that facilitate understanding the disease and the drug`s efficacy. The internal transcribed spacer (ITS) region was sequenced from three isolates, which were identified as Saprolegnia aenigmatica. Subsequently, healthy fish were immunosuppressed with dexamethasone (1.2 mg kg-1) and descaled to the skin using a sharp scalpel. These individuals were isolated in individual aquariums maintained at 22°C. Individuals in one group were subcutaneously inoculated with 9,000 zoospores (DDZ treatment), a second group was exposed to oomycetes in water with three colonized baits (DDB), a third group was maintained in water without zoospores (DD), and a control group (C) consisted of healthy animals. After 48 and 96 hours, two animals from each group were euthanized for fungal re-isolation. The fish from groups DD and C did not show clinical signs, and no oomycetes were isolated. The animals from the DDZ and DDB groups showed cotton-wool-like masses on the skin, and S. aenigmatica was re-isolated. Thus, for infection using zoospores or baits parasitized by S. aenigmatica, an immunosuppressor (dexamethasone) and a sharp scalpel can be used effectively to establish an experimental infection in P. mesopotamicus.